(untitled) (Journal of Engineering, 2022)
This study was done to investigate the impact of different nanoparticles on diesel fuel characteristics, Iraqi diesel fuel was supplied from al-Dura refinery and was treated to enhance performance by improving its characteristics. Two types of nanoparticles were mixed with Iraqi diesel fuel at various weight fractions of 30, 60, 90, and 120 ppm. The diesel engine was tested and run at a constant speed of 1600 rpm to examine and evaluate the engine’s performance and determine emissions. In general, ZnO additives’ performance analysis showed they are more efficient for diesel fuel engines than CeO. The performance of engine diesel fuel tests showed that the weight fraction of nanoparticles at 90 and 120 ppm give a similar performance, so, for economic aspects, the additives at 90 ppm of two types of nanoparticles gave good performance efficiency and the best reduction of gas emissions. The enhancement for ZnO additives is up to 34.28% compared to pure diesel fuel, while for nano CeO, the maximum enhancement is 20% compared to pure diesel fuel. The brake thermal efficiency increases with additives. The best improvements in brake thermal efficiency were 62% for ZnO and 59% for CeO, respectively, both at 120 ppm. A reduction in NOx, CO2, CO and UHC emissions was observed compared with the diesel fuel that was consumed from pure diesel fuel. The maximum reduction emissions values for NOx, CO, CO2 and un-burn hydrocarbon (UHC) were 63.77, 29.26, 56.41, and 57.37 % for ZnO, and 58.11, 37.80, 61.53, and 50.81 % for CeO additives. Therefore, it is recommended to utilize nanoparticles, especially ZnO, as a fuel additive with diesel fuel and consider them as an enhancer material to increase engine efficiency and reduce exhaust emissions.